Buletin Peternakan : FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN PEMASARAN SAPI POTONG DAN DAGING SAPI DI KABUPATEN ACEH BESAR - Hendra Koesmara, Sudi Nurtini, I Gede Suparta Budisatria (Peternakan UGM, 2015)
This research identified the forms of share market, to calculate the price received by farmers andÂ middlemen, and analyze marketing margins of beef cattle market. This research was conducted in June toÂ August 2011, in Aceh Besar regency of Aceh province. The method used in this study was a surveyÂ method and field direct observations and interviews using questionnaires to farmers, middlemen (mugge)Â and meat traders respondent. The number of samples were 420 respondents, including 270 respondentsÂ of livestock farmers,105 respondents of middlemen (mugee) and 45 respondents of meat traders (finalÂ consumer)from the three districts.